Comercio, sobreexplotación laboral y ciclos en la periferia: Una propuesta teórica y el caso ecuatoriano desde un modelo PVAR - John Cajas Guijarro; Bryan Pérez-Almeida (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– This paper theoretically interprets how international real capitalist competition pressures trade balances of the peripheral countries to depend on absolute cost advantages based on the super-exploitation of labor power and nature; dependence which creates cyclical dynamics within those countries. To reinforce such an interpretation, the paper takes as a study case the Ecuadorian peripheral capitalism, about which some historical-cyclical trends are presented as well as some examples of economic activities that seem to obtain their trade surplus through super-exploitation. Also, the paper estimates a PVAR model over a panel data of 43 economic activities observed during the period 2007-2016; from that estimation, it is found evidence of short-run cyclical dynamics among Ecuadorian economic activities. All the empirical results evidence the importance of the absolute cost advantages gained through super-exploitation of labor power and nature on the determination of trade balances and on the rise of cycles that reinforce the dependent condition of Ecuadorian capitalism.
Keywords: C33; F16; O11; 330; real competition; absolute cost advantages; super-exploitation; capitalist periphery; historical-cyclical trends; PVAR models